2018
DOI: 10.1590/1413-812320182311.24172016
|View full text |Cite
|
Sign up to set email alerts
|

Concerns about dental aesthetics are associated with oral health related quality of life in Southern Brazilian adults

Abstract: It aims to evaluate the association between dental appearance and Oral Health Related Quality of Life. Fifteen primary care services with dental services were selected in Porto Alegre, Brazil. Individuals were interviewed from a random sampling of households in the catchment area of the health centres. The outcome was having an OHIP14 score > 0 (any impact). The main exposures included self-reported tooth colour and position, perception of oral health and concern with dental aesthetics. Data were analysed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 24 publications
2
14
0
2
Order By: Relevance
“…To assess the impact on quality of life, the answers were dichotomized to the absence of impact (a sum equal to zero) and the presence of impact (when the sum was greater than zero) in the OHRQoL. 6,7 After the interview, the individuals were submitted to an oral examination to assess the number of natural teeth found in the oral cavity. The number of teeth was classified as ≤ 20 teeth or > 20 teeth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the impact on quality of life, the answers were dichotomized to the absence of impact (a sum equal to zero) and the presence of impact (when the sum was greater than zero) in the OHRQoL. 6,7 After the interview, the individuals were submitted to an oral examination to assess the number of natural teeth found in the oral cavity. The number of teeth was classified as ≤ 20 teeth or > 20 teeth.…”
Section: Methodsmentioning
confidence: 99%
“…4,5 The OHIP-14 questionnaire is an instrument used to analyze the impact of dental health on quality of life, and several studies found associations between oral health conditions and OHRQoL using the OHIP-14. 6,7,8,9 In addition, the use of tools that assess the individual's experience and perception of his or her health care during a particular procedure may itemize the characteristics of the procedure while also gathering data related to the health of the users. Patient-Reported Outcomes Measures (PROMs) provide information on the efficiency and effectiveness of services, patient satisfaction, and they assess the impact of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Por consiguiente, una salud bucal de ciente afectará negativamente a personas jóvenes, siendo la imagen estética la principal razón por la que el adolescente busca atención odontológica. Cuando la imagen social se ve perjudicada, se afecta su autoestima que inter ere en sus relaciones personales y vida social (37) .…”
Section: Discussionunclassified
“…1,2 It is also important because it can affect social relationships' through concerns with dental appearance. [3][4][5] Oral health and oral health-related quality of life (OHRQoL), which are explained by various individual, social and environmental factors, 6 can be improved with dental care. 7 Parents have a central role in shaping children's oral health behaviors because they depend upon adults, including access to oral health care 8,9 until they are sufficiently mature to form their own habits.…”
Section: Introductionmentioning
confidence: 99%